CONSUMER ACCEPTANCE OF NUTRITIONAL DATES SEED INNOVATION FOR A NEW ICE CREAM FLAVOR IN MALAYSIA - Razmah Mahmod; Mazni Saad; Faizah Mashahadi; Nazura Mohd Sayuti (International Journal of Accounting, Finance and Business, 2021)
Date fruit is a type of fruit grown mainly in the eastern region. Favourable researchfindings on date nutritional value have led to dates becoming one of the well-known fruitsconsumed by many people worldwide. In general, people only consume the date flesh but throwthe seed as waste. Recent studies have indicated nutritional benefits in date seed with potentialhealth benefits for human beings. In relation to promoting a green environment, this studyexamines consumer acceptance of the innovation of nutritional dates seed powder as the mainingredient in producing a new ice-cream flavour in Malaysia and determines the dates' nutrientcontent seed ice-cream mixture. The survey questions were adapted from the Nielsen GlobalNew Product Innovation Survey, Q1 2015, distributed through the Google form application.Of the 301 respondents randomly chosen, 94% agreed that dates seed ice cream was aninnovative food with nutritional value. In contrast, 84.7% were interested in buying the icecream if it was available in the market. The descriptive analysis indicated that the respondentsaccepted dates seed ice cream as a new ice-cream flavour with nutritional benefits. Indetermining the nutrient content of the seeds of the dates in the ice cream, a sample of the icecreammixture was sent to the SIRIM QAS laboratory for chemical analysis in August 2018.The findings showed that dates seed ice cream has a high nutrient content and calorie value,and since it contains no caffeine, it can be a substitute for coffee